Labile iron, ROS, and cell death are prominently induced by haemin, but not by non-transferrin-bound iron. (April 2022) - Imoto, Shion; Sawamura, Tohru; Shibuya, Yukiko; Kono, Mari; Ohbuchi, Ayako; Suzuki, Takashi; Mizokoshi, Yuji; Saigo, Katsuyasu
Abstract: Background: In transfusion-related iron overload, haem-derived iron accumulation in monocytes/macrophages is the initial event. When iron loading exceeds the ferritin storage capacity, iron is released into the plasma. When iron loading exceeds transferrin binding capacity, labile, non-transferrin-bound iron (NTBI) appears and causes organ injury. Haemin-induced cell death has already been investigated; however, whether NTBI induces cell death in monocytes/macrophages remains unclear. Material and Methods: Human monocytic THP-1 cells were treated with haemin or NTBI, particularly ferric ammonium citrate (FAC) or ferrous ammonium sulfate (FAS). The intracellular labile iron pool (LIP) was measured using an iron-sensitive fluorescent probe. Ferritin expression was measured by western blotting. Results: LIP was elevated after haemin treatment but not after FAC or FAS treatment. Reactive oxygen species (ROS) generation and cell death induction were remarkable after haemin treatment but not after FAC or FAS treatment. Ferritin expression was not different between the FAC and haemin treatments. The combination of an iron chelator and a ferroptosis inhibitor significantly augmented the suppression of haemin cytotoxicity (p = 0.011). Discussion: The difference in LIP suggests the different iron traffic mechanisms for haem-derived iron and NTBI. The Combination of iron chelators and antioxidants is beneficial for iron overload therapy.